2022
DOI: 10.1029/2021jc017799
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Modeling of a Buoyant Plume Exiting Into a Tidal Cross‐Flow and Exhibiting Along‐Front Instabilities

Abstract: Flows in and out of rivers and estuaries often generate dynamic frontal features due to localized sharp gradients in the currents, density, or bathymetry. Fronts often coincide with a narrow region of strong flow convergence, resulting in significant downwelling velocities and an increased surface roughness that make the fronts visible in remote sensing images. Within these energetic frontal zones and the shear layer at the density interface, shear instabilities are also common (Geyer et al., 2010;Horner-Devin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The obtained results on the different physical backgrounds of near-field and farfield instabilities are in a good agreement with the recent study of Simpson et al [41]. They also report the difference in sizes and vorticity patterns of lobe-and-cleft structures with and without velocity shear at the plume-sea interface, albeit that their numerical modeling limitedly addresses variability of sizes of these instabilities.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The obtained results on the different physical backgrounds of near-field and farfield instabilities are in a good agreement with the recent study of Simpson et al [41]. They also report the difference in sizes and vorticity patterns of lobe-and-cleft structures with and without velocity shear at the plume-sea interface, albeit that their numerical modeling limitedly addresses variability of sizes of these instabilities.…”
Section: Discussionsupporting
confidence: 91%
“…However, the depth of the vertical plume-sea interface within this stripe (1-1.5 m) was the same as in the surrounding plume. Simpson et al [41] also reported even greater increase in salinity in the plume in the vicinity of the lobe-and-cleft plume border from 5 to 13 (black line in Figure 8b in [41]).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Simpson et al. (2022) also observed discrepancies between the cross‐front scales of density and velocity in the tidal plume front of the Connecticut River, which they attributed at least in part to the challenge of resolving sharp velocity gradients. The difference in across‐front (convergent) velocity averaged 0.7 ± 0.1 m/s, whereas the difference in along‐front (sheared) velocity averaged 0.6 ± 0.1 m/s.…”
Section: Resultsmentioning
confidence: 99%